2021
DOI: 10.1002/pchj.498
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthy faces make people more risk‐tolerant: The effect of facial trustworthiness on risk decision‐making under gain and loss conditions

Abstract: People can judge a stranger's trustworthiness at first glance solely based on facial appearance. Moreover, the trust behaviors people exhibit toward strangers differ depending on perceived trustworthiness from faces. Research has found that people have different risk preferences according to the gain or loss frame. Therefore, we hypothesized that the risk decisions are differently affected by facial trustworthiness in different frames. We conducted three experiments in which we asked participants to make risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…On the other side, it was recently shown that wearing mask affects other perceived features, for example, it increases perceived attractiveness for both male and female stimuli ( Hies and Lewis, 2022 ; Parada-Fernández et al, 2022 ). Therefore, as attractiveness have been reported to increase perceived trustworthiness ( Pandey and Zayas, 2021 ) and trustworthiness have been proved to influence decision-making outcomes (e.g., Jaeger et al, 2019 ; Qi et al, 2021 ; Anzani et al, 2022 ), it can also be hypothesized that, through an indirect effect due to increased perceived attractiveness (already) untrustworthiness proposers are perceived as less untrustworthy and, therefore, a reduced effect on decision-maker’s discounting behavior should be detected. To deeper explore this phenomenon and investigate whether the presence of surgical mask produce a change on the effect of proposer’s trustworthiness on decision-making and to which extent, in the current work, we replicated the experimental procedure proposed by Anzani et al (2022) and conducted two separate experiments (experiment A investigating delay discounting and experiment B investigating probability discounting) after manipulating proposer’s stimuli to which a face surgical mask was applied.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, it was recently shown that wearing mask affects other perceived features, for example, it increases perceived attractiveness for both male and female stimuli ( Hies and Lewis, 2022 ; Parada-Fernández et al, 2022 ). Therefore, as attractiveness have been reported to increase perceived trustworthiness ( Pandey and Zayas, 2021 ) and trustworthiness have been proved to influence decision-making outcomes (e.g., Jaeger et al, 2019 ; Qi et al, 2021 ; Anzani et al, 2022 ), it can also be hypothesized that, through an indirect effect due to increased perceived attractiveness (already) untrustworthiness proposers are perceived as less untrustworthy and, therefore, a reduced effect on decision-maker’s discounting behavior should be detected. To deeper explore this phenomenon and investigate whether the presence of surgical mask produce a change on the effect of proposer’s trustworthiness on decision-making and to which extent, in the current work, we replicated the experimental procedure proposed by Anzani et al (2022) and conducted two separate experiments (experiment A investigating delay discounting and experiment B investigating probability discounting) after manipulating proposer’s stimuli to which a face surgical mask was applied.…”
Section: Introductionmentioning
confidence: 99%
“…When interacting with a stranger, people may form their first impression based on limited available information (e.g., facial appearance), and these judgments can subsequently and indirectly influence social decision making ( Qi et al, 2018 , 2021 ; Li et al, 2021 ). Many studies demonstrate that facial attractiveness has an impact on various social decisions, such as friendship and mating choices ( Thornhill and Gangestad, 1999 ), monetary decision-making ( Pandey and Zayas, 2021 ), and hiring ( Luxen and Van De Vijver, 2006 ).…”
Section: Introductionmentioning
confidence: 99%